2023
DOI: 10.3390/plants12244187
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid Modulates the Osmotic System and Photosynthesis Rate to Enhance the Drought Tolerance of Toona ciliata

Qi Gao,
Yamin Liu,
Yumin Liu
et al.

Abstract: Toona ciliata M. Roem. is a valuable and fast-growing timber species which is found in subtropical regions; however, drought severely affects its growth and physiology. Although the exogenous application of salicylic acid (SA) has been proven to enhance plant drought tolerance by regulating the osmotic system and photosynthesis rate, the physiological processes involved in the regulation of drought tolerance by SA in various plants differ. Therefore, drought mitigation techniques tailored for T. ciliata should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
(54 reference statements)
0
0
0
Order By: Relevance
“…Furthermore, under water restriction, it is also important to highlight that cowpeas can accumulate osmoprotective molecules, such as proline ( Santos et al., 2022 ) and total soluble sugars ( Jales Filho et al., 2023 ). These compounds favor water absorption, especially in low water availability soils, and are key mechanisms for plants to resist drought stress ( Mohammadi et al., 2019 ; Santos et al., 2022 ; Gao et al., 2023 ; Jales Filho et al., 2023 ). In our study, we observed a similar response in the cultivars BRS Tapaihum, BRS Pujante, and BRS Pajeú.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, under water restriction, it is also important to highlight that cowpeas can accumulate osmoprotective molecules, such as proline ( Santos et al., 2022 ) and total soluble sugars ( Jales Filho et al., 2023 ). These compounds favor water absorption, especially in low water availability soils, and are key mechanisms for plants to resist drought stress ( Mohammadi et al., 2019 ; Santos et al., 2022 ; Gao et al., 2023 ; Jales Filho et al., 2023 ). In our study, we observed a similar response in the cultivars BRS Tapaihum, BRS Pujante, and BRS Pajeú.…”
Section: Discussionmentioning
confidence: 99%